Comparative physical fitness profiles of female long-distance and sprint swimmers at Petrokima Gresik Club: A descriptive study - Kartika Jeaniar Fajar Nur Rahma (CV Rezki Media, 2025)
Background: Physical condition is a fundamental factor that affects swimmers' performance in developing techniques, tactics, and competition strategies, especially for swimmers specializing in different distances, such as sprinters and long-distance swimmers. Objectives: This study aims to analyze the dominant physical profiles of female sprinters and long-distance swimmers, providing evaluation material for coaches to develop more targeted training programs. Methods: The study employed a quantitative descriptive design, utilizing a survey and test approach. The research subjects consisted of 20 female swimmers from the Petrokimia Gresik Club who were selected purposively, including 10 sprinters and 10 long-distance swimmers. Data collection was conducted in 2024 through push-up tests (measuring arm muscle strength), sit-ups (assessing abdominal muscle strength), vertical jump (evaluating leg muscle explosive power), and multistage fitness tests (testing aerobic endurance). Raw scores were converted into t-scores and then categorized using the Norm Reference Scale (NRS). Data analysis was performed descriptively using means, standard deviations, and percentages. This study has obtained ethical approval from the relevant ethics committee. Results: The analysis results show that in the sprinter group, 4 out of 10 athletes (40%) were in the